A hydro - geophysical investigation of groundwater by electrical profiling - AFTHAB SAEED P. P; FAsludeen N. S; Dr. Kurien E.K (Guide) (Tavanur 2014 Department of Land and Water Resources & Conservation Engineering)
A hydro - geophysical investigation of groundwater by electrical profiling
A hydro - geophysical investigation of groundwater by electrical profiling